2020
DOI: 10.1002/clc.23308
|View full text |Cite
|
Sign up to set email alerts
|

Defining and managing patients with non‐ST‐elevation myocardial infarction: Sorting through type 1 vs other types

Abstract: Advances in cardiovascular (CV) imaging, redefined electrocardiogram criteria, and high‐sensitivity CV biomarker assays have enabled more differentiated etiological classification of myocardial infarction (MI). Type 1 MI has a different underlying pathophysiology than type 2 through type 5 MI; type 1 MI is characterized primarily by intracoronary atherothrombosis and the other types by a variety of mechanisms, which can occur with or without an atherosclerotic component. In type 2 MI, there is evidence of myoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 49 publications
0
20
0
1
Order By: Relevance
“…Although this could not explain all the inconsistency because subgroup analysis showed that ML also outperformed GRACE in STEMI in a previous study 11 , the different performances of the ML models between the STEMI and NSTEMI groups may have contributed to the inconsistent findings. The ML models may have higher discrimination in the NSTEMI group than the traditional model because NSTEMI has more heterogeneous clinical and pathological features than STEMI 22 , 23 . STEMI results from a complete thrombotic occlusion of the infarct-related artery, while NSTEMI occurs in more heterogeneous conditions, such as incomplete coronary occlusion, coronary artery spasm, coronary embolism, myocarditis, and others 24 .…”
Section: Discussionmentioning
confidence: 99%
“…Although this could not explain all the inconsistency because subgroup analysis showed that ML also outperformed GRACE in STEMI in a previous study 11 , the different performances of the ML models between the STEMI and NSTEMI groups may have contributed to the inconsistent findings. The ML models may have higher discrimination in the NSTEMI group than the traditional model because NSTEMI has more heterogeneous clinical and pathological features than STEMI 22 , 23 . STEMI results from a complete thrombotic occlusion of the infarct-related artery, while NSTEMI occurs in more heterogeneous conditions, such as incomplete coronary occlusion, coronary artery spasm, coronary embolism, myocarditis, and others 24 .…”
Section: Discussionmentioning
confidence: 99%
“…Total occlusion of a coronary artery induced by an eroded, vulnerable atherosclerotic plaque and the overlying thrombus formation might be a consequence of a hyperinflammatory environment along with the prothrombotic state induced by SARS-CoV-2 infection. This mechanism represents the basic pathophysiological substrate of ST-elevation myocardial infarction (STEMI) but also accounts for approximately 25% of cases admitted with non-ST-elevation myocardial infarction (NSTEMI) [ 42 , 43 ]. The real epidemiological impact of COVID-19 in patients with cardiac ischemia is mirrored by the worrisome incidence rates of myocardial infarction among SARS-CoV-2 positive cases, ranging from 1.1% to 8.9% [ 44 , 45 ].…”
Section: Cardiovascular Pathophysiology Related To Covid-19 and The M...mentioning
confidence: 99%
“…In recent years, the number of acute myocardial infarction (AMI) patients with non-ST-segment elevation myocardial infarction (NSTEMI) has been increasing. [1][2][3] NSTEMI is characterized by acute onset, hidden disease, many complications, and high mortality rate. Research on related factors affecting the prognosis of the disease has always been a hot spot in this field.…”
Section: Introductionmentioning
confidence: 99%